Homelessness and people with intellectual disabilities: A systematic review of the international research evidence - Mc Cann, Edward (My University, 2020)
Background: People with intellectual disabilities can experience homelessness and some of the reasons differ from the general homeless population. Specific policy and practice responses are required. Method: A systematic review of studies examining homelessness among people with intellectual disabilities utilizing CINAHL, MEDLINE, PsycINFO and Sociological Abstracts databases from inception to November 2019. Results: The search produced 259 papers and following screening a total of 13 papers were included in the review. The themes identified were (i) pathways into homelessness, (ii) experiencing homelessness, and (iii) routes out of homelessness. Conclusions: People with ID become homeless due to multifactorial issues. The identification of people within homeless services and their care and support concerns remains challenging, impacting upon the provision of assessments, interventions, care and supports. Psychosocial assessments, interventions and supports are necessary to assist people with ID to leave homelessness.
PUBLISHED
Keywords: Homelessness; Intellectual disabilities; Social exclusion; Stigma; Health needs; Supports; Inclusive Society; HOMELESSNESS; Homeless; Housing policy, homelessness; INTELLECTUAL DISABILITY